“Femvertising” and “Manufacturing consent” for the post-feminist smart entrepreneurial self: Badya’s Ramadan advertisement and campaign - Nashwa Elyamany (Cogent Arts & Humanities)
In this paper, I critically examine the idealized post-feminist entrepreneurial performance within elite semiotic landscapes and how these elements are jointly propagandized in the Egyptian TV advertisement and “Watch It” advertising campaign of Badya, an emerging neoliberally-oriented smart gated community in Egypt. Specifically, I explore: (a) the “entrepreneurial self” narratives that are strategically employed to project new neoliberal ideals for post-feminist performance within smart social spaces, and (b) the hybrid nuances of the entrepreneurial self that are semio-discursively constituted and mediated by the female lead characters in Badya’s femvertised promotional materials. To investigate the diverse incarnations of post-feminism and contribute to the “post” element in post-feminist discourse, I re-appropriate, re-conceptualize, and re-articulate Herman and Chomsky’s Propaganda Model. I propose the Elite Semiotic Landscape Propaganda Model (ESL-PM), which I apply to analyze the femvertising discourse within elite landscapes from a neoliberal-entrepreneurial perspective. Key findings reveal a quadripartite transition of the “Smart Entrepreneurial Self,” which materializes throughout the promotional materials as an aggregation of four facets: the aestheticized self, the athletic self, the agentive self, and the aspired self. These identities are co-opted and selectively emphasized in an intersectional manner, where the female lead character’s self-presentations intertwine multicultural, multimodal, and converging modes of spectatorship, along with unique constructions of transnational entrepreneurship.